Legal Consequences for Children Who Commit Criminal Acts of Terrorism Based on Law Number 5 of 2018 Concerning the Eradication of Criminal Acts of Terrorism - Andi Rief Irfandi; Anak Agung Gede Putra Arjawa; Ida Bagus Anggapurana (Sharia Oikonomia Law Journal, 2023)
Terrorism is an extraordinary crime (Extra Ordinary Crime), the international world created the concept of constitution through international conventions, namely the "Universal Declaration Of Human Rights" as a foundation of human rights, specifically the United Nations passed the "Convention On The Right Of The Child" to protect children and uphold children's human rights throughout the world. Terrorism eradication efforts of the government and the private sector are expected to focus on increasing integrated cooperation at all levels of society and creating the right legal concept for perpetrators of terrorism and legal certainty for children involved in criminal acts of terrorism. In this study using the Empirical Juridical research method is done by conducting legal research on the application of normative law directly on certain legal events that occur in society supported by data and facts. Descriptive Analysis, because the data collected in the form of words and images and not numbers that can provide a description of the subject of the research conducted, the data collected becomes a node of what has been researched. It can be concluded that the consequences of acts of terrorism result in losses in the form of loss of life, material, economic instability in the field of investment in the form of reduced foreign investors investing with security considerations and fear of loss.